If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
x^2+(1/6)*x = 0
x^2+1/6*x = 0
DELTA = (1/6)^2-(0*1*4)
DELTA = 1/36
DELTA > 0
x = ((1/36)^(1/2)-1/6)/(1*2) or x = (-(1/36)^(1/2)-1/6)/(1*2)
x = 0 or x = -1/6
x in { -1/6, 0 }
| 12+m-6=3m-4m | | -17+5x=3x+33 | | -152-6x=46+5x | | 3a+4b+5c= | | -47+6x=33+11x | | -68+11x=-x+112 | | -9x-107=3x+73 | | 3x-123=9x+57 | | -7x-101=3x+99 | | 8x-35=69+12x | | 24x+4=6 | | 4a+3b-2c= | | 10-x=8x-10 | | 4=-4x+3x+9 | | x+42x=24 | | X^2/4-x=15 | | 8x+13y=130whatisx+y | | X-3-4x=27 | | z=7a/9*4/2a | | 2y-18/6=4y+3 | | C-2=3c+24 | | y^2+16y+48=0 | | -3x+4=27 | | -14=-7r-7 | | 9=-7+4-6k | | 6856.9-6978.0= | | 10x-1=4x-31 | | 8n-4/1+2n | | Y=x^2(x^5-x) | | 26+x=3x | | x^2+170=49 | | 5x+(-3x-1)=4x+(x-1) |